The Influence of Lifestyle Against Purchase Decision of ICONinety9 Products In Pekanbaru (Case Study on ICONinety9 Shop In Mall SKA and CIPUTRA) - Mismay Debora; Lilis Sulistyowati; Aida Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted on ICONinety9 Shop In Mall SKA and CIPUTRA in order to analyze the influence of lifestyle variable by consist of activity, interest and opinion on the purchasing decision of ICONinety9 Products In Pekanbaru. Intake number of samples was done by using a formula approach Hair by respondents as many as 102 people and using purposive sampling and proportionate stratified sampling techniques. The analytical method used is descriptive method, the data analysis carried out simultaneously and partial (multiple linear regression analysis with SPSS version 18.0). From the results of simultaneous testing (test F) known that Fhitung (28,955) > Ftabel (2,697). It means that all independent variables studied, namely activity, interest and opinion has a significant effect on the dependent variable is the purchase decision. Partial regression test (test t) showed that the opinion variable is the variable that most influence the purchase decisions of ICONinety9 Products when compared with variable activity and interest. The magnitude of the effect caused by the three independent variables on the dependent variable was (0,454) this means that the variable activity, interest and opinion jointly influence the purchase decision variable percentage of 45,4%. While 54,6% is influenced by other variables that are not addressed in this research. It can be concluded that the variable activity, interest and opinion simultaneously and partially positive and significant impact on the purchasing decisions of ICONinety9 Products In Pekanbaru.Keywords: Activity, Interest, Opinion and Purchase Decision